Effects of mineral complex material treatment on 2,4- dinitrochlorobenzene-induced atopic dermatitis like-skin lesions in mice model - Johny Bajgai; Jing Xingyu; Ailyn Fadriquela; Rahima Begum; Dong Heui Kim; Cheol-Su Kim; Soo-Ki Kim; Kyu-Jae Lee (BMC, 2021)
Abstract Background Atopic dermatitis (AD) is a chronic allergic inflammatory skin disease characterized by complex pathogenesis including skin barrier dysfunction, immune-redox disturbances, and pruritus. Prolonged topical treatment with medications such as corticosteroids, calcineurin inhibitors, and T-cell inhibitors may have some potential side-effects. To this end, many researchers have explored numerous alternative therapies using natural products and mineral compounds with antioxidant or immunomodulatory effects to minimize toxicity and adverse-effects. In the current study, we investigated the effects of mineral complex material (MCM) treatment on 2, 4-dinitrochlorobenzene (DNCB)-induced AD-like skin lesions in SKH-1 hairless mice. Methods Animals were divided into four groups; normal control (NC), negative control treated with DNCB only (DNCB only), positive control treated with DNCB and tacrolimus ointment (PC) and experimental group treated with DNCB and MCM patch (MCM). Skin inflammation and lesion severity were investigated through analyses of skin parameters (barrier score and strength, moisture and trans-epidermal water loss level), histopathology, immunoglobulin E, and cytokines. In addition, reactive oxygen species (ROS), nitric oxide (NO), glutathione peroxidase (GPx), and catalase (CAT) levels were measured in both serum and skin lysate. Results Our results demonstrates that MCM patch improved the progression of AD-like skin lesions by significantly increasing skin barrier strength and decreasing trans-epidermal water loss. Additionally, dermal administration of MCM patch significantly reduced epidermal thickness, ROS, and NO levels in skin lysate. Furthermore, we found that MCM suppressed the levels of AD-involved (Th1 and Th2) cytokines such as IL-2, IFN-γ, and IL-4 in blood. In addition, the levels of other Th1, and Th2 and inflammatory cytokines such as IL-1β, TNF-α, IL-6, IL-12(p70) and IL-10 were found lowest in the MCM group than in the DNCB only and PC groups. Moreover, we found total serum IgE level significantly increased after DNCB treatment, but decreased in the PC and MCM groups. Conclusion Taken together, our findings suggest that MCM application may have beneficial effects either systemic or regional on DNCB-induced AD lesional skin via regulation of the skin barrier function and immune-redox response.